التدابير القرآنية التي تمكن الأسرة الصومالية المسلمة من الحفاظ على هويتها في المهجر: Quranic measures that enable the Somali Muslim family to preserve its identity in the diaspora - Qassim Ali, Rahma; Jamal Elatrash, Radwan (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف هذا البحث إلى إيجاد التدابير القرآنية التي تمكن للأسر الصومالية المسلمة من استخدامها للمحافظة على هويتها الإسلامية في المهجر، وذلك في ظل الضغوط الثقافية والإعلامية والاجتماعية المتزايدة عليها هناك، ولتحقيق ذلك اعتمد البحث على المنهج الاستقرائي من خلال جمع الآيات القرآنية، والأحاديث النبوية الشريفة التي تحدثت عن الهوية، وإبراز خصائصها ومقوماتها التي جاءت في القرآن الكريم والسنة النبوية، وكذلك ما تناوله الكتّاب العرب من مكائد الغرب تجاه هذه القضية، وكذلك المؤلفات التي تحكي واقع الأسرة الصومالية في المهجر، كما تم الاعتماد على المنهج التحليلي لبيان أهمية الحفاظ على الهوية الإسلامية في ضوء الآيات القرآنية وتفسيرها مستعينة بأقوال المفسرين والعلماء، ومن ثم تحليلها واستنباط دلالاتها، وقد خلص البحث إلى عدة نتائج منها: أن الهوية الإسلامية هبة إلهية من الله تعالى، وهي فريدة لا تتجزأ؛ لأنها هويةٌ واحدةٌ لا تتغير، ولا تتبدل، ولا تتنوع ولا تمتزج مع غيرها، ولكنها تقبل التعايش مع الهويات الأخرى. كما أثبت البحث أن الغرب يتسم بالتناقض تجاه هويات الآخرين، حيث يشعر بالفخر والاعتزاز بهويته من جهة، بينما يرفض من جهة أخرى الاعتراف بالهويات الوطنية للشعوب الأخرى. ABSTRACT This study aims to identify Qur'anic measures that Somali Muslim families can employ to preserve their Islamic identity while living abroad, in the face of mounting cultural, media, and social pressures. To achieve this, the study employs an inductive approach by collecting Qur'anic verses and Hadiths related to the concept of identity, highlighting its characteristics and foundations as articulated in the Qur'an and Sunnah, along with examining Arab scholars' insights on Western challenges to Islamic identity. The study also reviews literature on the experiences of Somali families in the diaspora. An analytical method is used to underscore the importance of preserving Islamic identity through Qur'anic verses and their interpretations, supported by scholars' exegeses, followed by a thorough analysis and extraction of relevant meanings. The study concludes with several findings, including that Islamic identity is a divine gift from Allah, unique and indivisible; it is a singular identity that does not change, transform, diversify, or blend with other identities, although it can coexist peacefully alongside them. Furthermore, the study reveals a contradictory stance in the West regarding other identities; while proud of its own, the West often refuses to recognize the national identities of other peoples.